2019
DOI: 10.1016/j.vacuum.2019.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Phase composition and mechanical properties of Cu–Ti alloys synthesized in the surface layer of copper by plasma impact on the Ti/Cu system

Abstract: Cu-Ti alloys synthesized in the surface layer of copper by means of preliminary Ti coating deposition and subsequent treatment by compression plasma flows have been investigated in this work. X-ray diffraction, scanning electron microscopy, energy-dispersion X-ray microanalysis, Auger electron spectroscopy, Vickers microhardness measurements and tribological tests were used for Cu-Ti alloys characterization. The findings showed that the increase of the energy absorbed by the surface layer during plasma treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The concentration of copper decreased with the growth of the energy density absorbed by surface layer, that is associated with the erosion of the surface layer under plasma exposure and increase of the molten layer thickness (Cherenda et. al., 2015, Cherenda et. al., 2019.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of copper decreased with the growth of the energy density absorbed by surface layer, that is associated with the erosion of the surface layer under plasma exposure and increase of the molten layer thickness (Cherenda et. al., 2015, Cherenda et. al., 2019.…”
Section: Resultsmentioning
confidence: 99%
“…The change of mechanical and physical properties is attributed to the increase of intermolecular distance caused by thermal expansion, which leads to the increase of viscosity and the adhesion friction coefficient of titanium alloys. It has also been reported that high temperatures promote the diffusion of oxygen atoms, leading to the oxidation of Ti and Cu atoms in the metal [ 23 ]. TiO 2 oxide is also a kind of hard phase which may aggravate abrasive wear.…”
Section: Resultsmentioning
confidence: 99%
“…CPF irradiation experiments were performed at distances of about 16, 12 and 8 cm, respectively. Based on experimental results and prior experience [12,40], energy densities of the above irradiation were estimated to be about 20, 50 and 80 J cm −2 , and the corresponding power densities were about 2, 5 and 8 GW m −2 . The evolution of temperature, stress and strain with time and space in tungsten and molybdenum during CPF irradiation was simulated by the finite element method using Abaqus software.…”
Section: Methods Of Experiments and Simulationmentioning
confidence: 96%